Vertical stratification of plant-pollinator interactions in a temperate grassland - Klecka, Jan; Hadrava, Jiří; Koloušková, Pavla (PeerJ Preprints, 2018)
Visitation of plants by different pollinators depends on individual plant traits, spatial context, and other factors. A neglected aspect of small-scale variation of plant-pollinator interactions is the role of vertical position of flowers. We conducted a series of experiments to study vertical stratification of plant-pollinator interactions in a dry grassland. We observed flower visitors on cut inflorescences of Centaurea scabiosa and Inula salicina placed at different heights above ground in two types of surrounding vegetation: short and tall. Even at such a small-scale, we detected significant shift in total visitation rate of inflorescences in response to their vertical position. In short vegetation, inflorescences close to the ground were visited more frequently, while in tall vegetation, inflorescences placed higher received more visits. Moreover, we found major differences in the composition of the pollinator community on flowers at different heights. In a second experiment, we measured flower visitation rate in inflorescences of Salvia verticillata of variable height. Total flower visitation rate increased markedly with inflorescence height in this case. Data on seed set of individual plants provide evidence for a corresponding positive pollinator-mediated selection on increased inflorescence height. Overall, our results demonstrate strong vertical stratification of plant-pollinator interactions at the scale of mere decimetres. This may have important ecological as well as evolutionary implications.
Keywords: pollination; plant-pollinator interactions; entomology; foraging biology; plant reproduction; bees